Fostering Moderate Islamic Education: The Strategic Role of the Cinta Rasul Majelis Ta’lim at Ribath Pesantren in Garut - Lailiyah, Muizatul; Rofiq, Mohammad (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
This research highlights the importance of strengthening religious moderation in Islamic education as an effort to maintain social harmony within a pluralistic society. The aim of the study is to analyze the role of the Nusantara Cinta Rasul Islamic Study Assembly at Ribath Garut Islamic Boarding School in developing Islamic education based on religious moderation. The object of the research is the Nusantara Cinta Rasul Assembly and the environment of the Ribath Garut Boarding School. This study employs a field research method with a qualitative descriptive approach. The data sources consist of primary data in the form of interviews, observations, and documentation, as well as secondary data from relevant literature. Data analysis was carried out interactively through the process of reduction, presentation, and inductive conclusion drawing. The results show that the Nusantara Cinta Rasul Assembly and the Ribath Garut Boarding School have successfully integrated the values of religious moderation into the curriculum and inclusive, dialogical teaching methods. Various programs such as religious studies, inter-organizational forums, and social activities have served as effective means to instill attitudes of tolerance, justice, and respect for differences. Despite facing challenges such as polarization and limited resources, both institutions remain consistent in innovating and collaborating to create a harmonious and moderate Islamic educational environment.